2020
DOI: 10.1111/jop.13007
|View full text |Cite
|
Sign up to set email alerts
|

HSP105 expression in oral squamous cell carcinoma: Correlation with clinicopathological features and outcomes

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“… 6 , 20 Another study suggested that increased expression of HSP105 in oral squamous cell carcinoma could be an unfavorable factor for malignancy. 7 These findings are consistent with our results. We believe that poorly differentiated CSCC cells exhibit a significantly faster rate of cell aggregation and proliferation with a higher proliferation index, which may be related to higher expression of HSP105, which may function to help cancer cells maintain functional integrity during tumor proliferation and prevent apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 6 , 20 Another study suggested that increased expression of HSP105 in oral squamous cell carcinoma could be an unfavorable factor for malignancy. 7 These findings are consistent with our results. We believe that poorly differentiated CSCC cells exhibit a significantly faster rate of cell aggregation and proliferation with a higher proliferation index, which may be related to higher expression of HSP105, which may function to help cancer cells maintain functional integrity during tumor proliferation and prevent apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have revealed that HSP105 is overexpressed in CSCC and oral SCC. 7 , 8 The present work shows, for the first time to our knowledge, a lower expression of HSP105 in CSCC compared to the normal epidermis. These findings suggest that HSP105 may play different roles in different tumors and merit further investigation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Most malignant melanomas exhibit increased expression of iASPP (inhibitor of an apoptosis-stimulating protein of p53) [ 7 ], while HSP105 can bind to the tumor suppressor gene p53 to protect cells from apoptosis, which is essential for the survival and proliferation of cancer cells [ 8 10 ]. HSP105 was shown to be overexpressed in a variety of human cancer cells, and high expression of HSP105 in squamous cell carcinoma [ 11 ], lung adenocarcinoma [ 12 ] and oral squamous cell carcinoma [ 13 ] is always related to disease progression and poor prognosis. Although several studies have revealed that HSP105 expression in CMM and metastatic CMM is higher than that in nevi [ 14 ], the relationship between HSP105 and clinicopathological features of CMM has not been identified.…”
Section: Introductionmentioning
confidence: 99%